Activation of mesolimbic reward system via laterodorsal tegmental nucleus and hypothalamus in exercise-induced hypoalgesia - Kami, Katsuya (Sci Rep, 2018)
Ventral tegmental area (VTA) dopamine (DA) neurons are the primary source of dopamine in target structures that constitute the mesolimbic reward system. Previous studies demonstrated that voluntary wheel running (VWR) by neuropathic pain (NPP) model mice produces exercise-induced hypoalgesia (EIH), and that activation of mesolimbic reward system may lead to EIH. However, the neuronal mechanism by which the mesolimbic reward system is activated by VWR is unknown. Here, we found that VWR produces EIH effects and reverses the marked reduction in activated lateral VTA (lVTA)-DA neurons induced by NPP. The proportions of activated laterodorsal tegmental nucleus (LDT)-cholinergic and lateral hypothalamus-orexin neurons were significantly enhanced by VWR. Retrograde tracing and dual immunostaining revealed that VWR activates lVTA-projecting LDT-cholinergic/non-cholinergic and lateral hypothalamic area (LHA)-orexin/non-orexin neurons. Therefore, EIH effects may be produced, at least in part, by activation of the mesolimbic reward system via activation of LDT and LHA neurons.